Patterns of spatial and temporal distribution of humpback whales at the southern limit of the Southeast Pacific breeding area. - Chiara Guidino; Miguel A Llapapasca; Sebastian Silva; Belen Alcorta; Aldo S Pacheco (PLoS ONE, 2014)
Understanding the patterns of spatial and temporal distribution in threshold habitats of highly migratory and endangered species is important for understanding their habitat requirements and recovery trends. Herein, we present new data about the distribution of humpback whales (Megaptera novaeangliae) in neritic waters off the northern coast of Peru: an area that constitutes a transitional path from cold, upwelling waters to warm equatorial waters where the breeding habitat is located. Data was collected during four consecutive austral winter/spring seasons from 2010 to 2013, using whale-watching boats as platforms for research. A total of 1048 whales distributed between 487 groups were sighted. The spatial distribution of humpbacks resembled the characteristic segregation of whale groups according to their size/age class and social context in breeding habitats; mother and calf pairs were present in very shallow waters close to the coast, while dyads, trios or more whales were widely distributed from shallow to moderate depths over the continental shelf break. Sea surface temperatures (range: 18.2-25.9°C) in coastal waters were slightly colder than those closer to the oceanic realm, likely due to the influence of cold upwelled waters from the Humboldt Current system. Our results provide new evidence of the southward extension of the breeding region of humpback whales in the Southeast Pacific. Integrating this information with the knowledge from the rest of the breeding region and foraging grounds would enhance our current understanding of population dynamics and recovery trends of this species.